Correlation of thyroid status with severity of hypertension in pregnancy - Rani Kumari; Kumari Archana; Roopam Singh; Rita Tirkey (International Journal of Health and Clinical Research, 2021)
Introduction:Thyroid dysfunction constitutes major endocrine disorders during Pregnancy. It has long been recognized that maternal thyroid hormone excess or deficiency can influence maternal outcomes like miscarriages, anaemia in pregnancy, preeclampsia,abruptio placenta and postpartum haemorrhage and foetal outcome at all stages of pregnancy like prematurity, low birth weight, increased neonatal respiratory distress and foetal thyroid abnormalities which may justify screening for thyroid functions in pregnancyThis study was conducted to see the possible relationship between preeclampsia andthyroid dysfunctionMethod: The study was a prospective, randomized, observational, case – control study on 216 patients conducted in the department of Obstetrics and Gynaecology, Bokaro General Hospital,Bokaro, Jharkhand,from July – 17 to December – 18.Observation and results:No of clinical hypothyroid cases were 12% in severe preeclampsia and while there was no case of clinical hypothyroidism in gestational hypertension.In sub clinical hypothyroid cases was 48% & 20% of severe preeclampsia and gestational hypertension respectively.Conclusion:A positive association was found between thyroid hypofunction and pregnancy induced hypertension in the present study.